The Evaluation of Plantation Development Policy in the City of Tidore Island - Isra Muksin (Yayasan Ilomata, 2023)
The purpose of this study is to evaluate the policy of providing assistance in the form of seeds for agriculture in Oba District, the city of Tidore Island. The research method used is descriptive qualitative in which an interview with 35 farmers from 12 villages and 1 sub-district is conducted. The results indicate that the policy on seeds provision to farmers in the city of of Tidore Island has been on target, yet it has not been successful due to inadequate support given concerning the ongoing guidance and supervision, therefore most of the seeds received are not planted. Another research finding is that the role of Gapoktan (Gabungan Kelompok Tani Farmers Group Association) in every village of Oba District is not optimum since access to information regarding facilities and infrastructure is limited.